An optimized procedure for preparation of conditioned medium from Wharton’s jelly mesenchymal stromal cells isolated from umbilical cord - Acuto, Santina; Lo Iacono, Melania; Baiamonte, Elena; Lo Re, Rosa; Maggio, Aurelio; Cavalieri, Vincenzo (Frontiers in Molecular Biosciences, 2023)
Cell-free therapy based on conditioned medium derived from mesenchymal stromal cells (MSCs) has gained attention in the field of protective and regenerative medicine. However, the exact composition and properties of MSC-derived conditioned media can vary greatly depending on multiple parameters, which hamper standardization. In this study, we have optimized a procedure for preparation of conditioned medium starting from efficient isolation, propagation and characterization of MSCs from human umbilical cord, using a culture medium supplemented with human platelet lysate as an alternative source to fetal bovine serum. Our procedure successfully maximizes the yield of viable MSCs that maintain canonical key features. Importantly, under these conditions, the compositional profile and biological effects elicited by the conditioned medium preparations derived from these MSC populations do not depend on donor individuality. Moreover, approximately 120 liters of conditioned medium could be obtained from a single umbilical cord, which provides a suitable framework to produce industrial amounts of toxic-free conditioned medium with predictable composition.